Biodegradable cutting fuids for sustainable manufacturing: a review of machining mechanisms and performance - Liew, Pay Jun; Gan, Chin Ket; Kin, Yuen Leong; Yan, Jiwang (Springer Nature, 2024)
The application of biodegradable cutting fuids in metal cutting processes has raised interest among multidisciplinary researchers. Vegetable oils with long and polar fatty acid chains provide thick lubricant coatings that interact strongly with metallic surfaces, making them ideal biodegradable cutting fuids. In this review, the viscosity, oxidation performance, and machining performance of several vegetable oils, including palm, coconut, neem, and jatropha oils, were analysed and compared with conventional cutting fuids. The associated challenges in this feld are discussed, and future research directions presented. Through this review, vegetable oils with particle additives, like alumina, silicon dioxide, molybdenum disulfde, and hexagonal boron nitride, were identifed to be capable of improving the machining performance. The particles’ mending, polishing, and rolling efects are efective mechanisms for improving machining performance. Furthermore, chemical modifcation processes, such as transesterifcation and epoxidation, improve the anti-oxidation ability of vegetable oils by altering the carboxyl group (esterifcation/transesterifcation) or the fatty acid chain (epoxidation). Consequently, vegetable oils with particle additives and chemical modifcation surpass conventional cutting fuids in metal cutting operations and contribute to sustainable manufacturing technologies.